Exergy assessment of single and dual pressure industrial ammonia synthesis units. (15th December 2017) - Flórez-Orrego, Daniel; de Oliveira Junior, Silvio
Abstract: In exothermic, equilibrium-limited processes such as ammonia synthesis, higher per-pass conversions are often achieved by withdrawing the enthalpy of reaction before the conversion has been completed. However, although inter-bed cooling may help controlling the bed feed temperatures and generates high pressure steam, it also shifts the reacting mixture away from equilibrium (i.e. by increasing the reacting driving force, -ΔG), thus increasing the process irreversibilities. In order to offset the unfavorable effects of the bed intercooling in the decreasing-volume reactive system as well as to reduce the power consumption, a catalytic once-through conversion section is introduced in a 1000 metric tNH3 /day ammonia synthesis unit. Three unit configurations are analyzed: two are based on single pressure loops (SP150, SP200), whereas the other one (DP) operates at two incremental levels of pressure (83/200 bar). The dual pressure process aims to show the relevance of the Counteraction Principle for driving the system irreversibilities down. The plant-wide and main components' performance are also compared in terms of exergy efficiency, economic revenues and utilities consumption. As a result, the syngas compressor, ammonia converter, waste heat recovery and ammonia refrigeration systems are found to be responsible for about 80–86% of total irreversibilities in the ammonia loop, which varies from 23.8 MW for DP and 27.2 MW for SP150. A cryogenic purge gas treatment unit allows improving the loop performance in 9–13% if compared to non-hydrogen-recovery systems. Highlights: The favorable effect of introducing a catalytic once-through conversion section is studied. The dual pressure process allows driving the irreversibilities down 12% by using a counteraction. The strong relationship between the irreversibilities and reactor performance is highlighted. The overall exergy destruction rates attain 27 MW for which potential mitigation steps are discussed. Some improved performance indicators for the plant and for various components are proposed.